UK air transport policy in the context of Europe one day conference Thursday 1 June 2000 : delegate information (Thomas Telford, 2000)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Conference paper presented on 1 June 2000.